Character Values Analysis of Students' English Textbook Entitled - Vita Nurul Hidayah (Universitas Ahmad Dahlan, 2022)
Indonesian schools have to think about the strict the re orientation of character values, attitudes, and characters in education. The school plays a major role in shaping students’ values, because most of their times are spent in school with their teachers and classmates. English language teaching should not just give knowledge about language, but also character input. One of the important things here is the textbook used. Therefore, this descriptive qualitative research aims to find, explore, as well as analyze character values, techniques in integrating of English textbook in English textbook titled “Contextual English for Grade X of Senior High School Regular Program” and strategies